1984
DOI: 10.2170/jjphysiol.34.369
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine decreases single channel conductance of inward rectifier K channel in mammalian ventricular myocytes.

Abstract: Summary Effect of lysophosphatidylcholine (LPC) on the inward rectifier K channel of the isolated guinea pig ventricular cell was studied using patch clamp technique. In that LPC (100 ,uM) decreased the magnitude of the single channel conductance from 48±5 pS (mean and S.D., n=5) to 12±9 pS (n=8), this event may be the prime factor related to the alleged LPC-induced depolarization of cardiac tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
2
8
2
Order By: Relevance
“…Once the rapid phase of membrane depolarization occurred the effects of LPC were irreversible. Qualitatively similar results were obtained in four myocytes exposed to 20 AtM LPC at 350C, as illustrated in the lower panels of Fig. 3.…”
Section: Methodssupporting
confidence: 85%
See 4 more Smart Citations
“…Once the rapid phase of membrane depolarization occurred the effects of LPC were irreversible. Qualitatively similar results were obtained in four myocytes exposed to 20 AtM LPC at 350C, as illustrated in the lower panels of Fig. 3.…”
Section: Methodssupporting
confidence: 85%
“…In intact ventricular muscle and Purkinje fibers, electrophysiological effects of lysophosphoglycerides include decreases in diastolic resting potential, action potential amplitude and duration, and the appearance of abnormal automaticity, delayed afterdepolarizations, and triggered activity (13)(14)(15)(16)(17)(18). Similar effects have been described in single ventricular myocytes (19,20). Many of these effects are suggestive of intracellular Ca2+ overload, and Sedlis et al (21,22) showed that lysophosphoglycerides induced an increase in total intracellular Ca2" measured with 45Ca2+.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations